Internet Addiction and its Affecting factors among Undergraduate Students: An Integrative Review (International Journal of Nursing Education, 2021)
Background: This contemporary technological era is witnessing internet addiction as an emergingglobal concern and burden on mental health and society. It is a multidimensional phenomenon thataffects an individual physically, psychologically, and socially.Objective: The objective of this review was to describe internet addiction and examine its affectingfactors among undergraduate university students.Methods: This integrative review was conducted to examine the affecting factors related to internetaddiction among university students using PRISMA guidelines.A systematic search was conductedusing Academic Search Complete (EBSCO), PubMed, MEDLINE, APA PsycArticles, CINAHL,SCOPUS, google scholar, ScienceDirect published in the English language between the year January2011 to January 2021.Results: A total of seventeenarticles were retrieved and their results were synthesized. The findingsrevealed three common measurement tools namely Internet Addiction Test (IAT), Young’s DiagnosticQuestionnaire (YDQ), and Chen’s Internet Addiction Scale (CIAS). Two factors were found relatedto internet addiction, internal factors that include demographic factors and psychological factors andexternal factors like external financial funding, and internet accessibility in college.Conclusion:As internet addiction leads to many psychiatric comorbidities, identification of thefactors contributing to this phenomenon needs more attention and careful consideration for preventionstrategies.
Keywords: Internet addiction, University students, Factors, Integrative review.